Cohabitation and Religious Marriage : Status, Similarities and Solutions - Akhtar, Rajnaara (Book collections on Project MUSE., 2020)
Cohabiting couples and those entering religious-only marriages often end up with inadequate legal protection when the relationship ends. Based on wide-ranging empirical studies, this book explores the complexities of the law, the different ways in which individuals navigate the gaps in the existing legal framework and solutions for reform.